Exploring the Role of Mass Media in Enhancing Farmer-to-Farmer Extension Activities in Bosomtwe District, Ghana - Anthony K. Appiah; Enoch K. Tham-Agyekum; Fred Nimoh; John-Eudes A. Bakang; Fred Ankuyi (Journal of Human Sciences and Extension)
Farmer-to-farmer extension has always existed among farmers. It helps to strengthen information flow, reduce extension costs, and empower farmers playing a crucial role in enhancing their livelihoods. Currently, scanty information exists on the role of mass media in enhancing farmer-farmer extension activities. It is against this background that this study was carried out. Descriptive and inferential statistics were used to analyze data from 400 farmers who were selected using the multi-stage sampling technique. The results show that, compared to newspapers, books, TV, radio, computers, and social media, the mobile phone is the most accessible and most used mass media tool among farmers. Farmers use mass media mainly to create awareness of agricultural products and services. Education is a key factor influencing the accessibility and use of print, outdoor, and digital/new-age media. Access to extension positively influences accessibility and use of broadcast and digital/new age media. Farmers agreed that the high cost of purchasing mass media tools and insufficient capital to buy them were the main constraints they faced in effectively using mass media to communicate among themselves. Farmers need to be trained and educated to make good use of other mass media tools to strengthen information flow.